Development of Lembar Kerja Peserta Didik (LKPD) Based on Contextual Teaching and Learning (CTL) on Environmental Pollution Material Class VII SMP Negeri 4 Botomuzoi Academic Year 2022/2023 - Balazi Lase; Desman Telaumbanua (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to: 1) Know the feasibility of CTL (Contextual Teaching and Learning) based Lembar Kerja Peserta Didik (LKPD) 2) Know the practicality of CTL (Contextual Teaching and Learning) based Student Worksheets (LKPD) and 3) Know the effectiveness of the Lembar Kerja Peserta Didik (LKPD) Lembar Kerja Peserta Didik (LKPD) based on CTL (Contextual Teaching and Learning). The type of research used is development research which refers to the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation). The instruments used were validation questionnaires, student response questionnaires and learning outcomes tests. Data analysis techniques using quantitative descriptive. The results of the study consisted of: 1) The feasibility of CTL (Contextual Teaching and Learning)-based worksheets for material validators by lecturers was 82% with very appropriate criteria, 85.5% for material validators by teachers with very feasible criteria, the results of language validation were 66% with feasible criteria and design validation by the design validator is 84% very feasible criteria. 2) The practicality of CTL (Contextual Teaching and Learning)-based LKPD through student responses for individual tests 90% with very practical criteria, 85% for small group tests with very practical criteria and 92% for field trials with very practical criteria. 3) The effectiveness of CTL (Contextual Teaching and Learning)-based LKPD is 87% with very effective criteria.